Investigating the impact of Learning English as a foreign language on creative writing skills amongst gifted secondary students in national and international private Schools in Alhasa (A case study) - Alhassan, Albandary Abdullah (Journal of Curriculum and Teaching Methodology, 2023)
This research project aims to investigate the impact of learning English as a foreign language on developing the creative writing skill of gifted female students at secondary level in the Kingdom of Saudi Arabia. The case study included the questionnaire in its three sections and an analysis of the written texts of the students. The data were analyzed using frequencies, arithmetic averages, and t-test to find out the differences between the performances of the two groups using the SPSS statistical analysis program. The study found that there are no statistically significant differences between the performance of gifted female students in the national program and gifted female students in the international program. The students’ self-assessment of their creative writing skill revealed the students’ preference for writing in English, which supports the positive impact of second language learning on developing the creative writing skill of gifted students in general.